LEARNING TO BECOME UZBEKISTANI: SCHOOLING AND YOUTH DISCOURSES OF NATIONAL IDENTITIES THROUGH THE INTERSECTIONS OF ETHNICITY, GENDER AND RELIGION - Ozawa, Vanessa Caroline (Nazarbayev University Graduate School of Education, 2025)
Since 1991, Uzbekistan, a multi-ethnic Central Asian state where 60% of the population is under 30, has placed youth at the centre of nation-building. Intending to fill the void left by socialist ideologies, constructing a new national identity has become a political priority. As powerful state institutions where “official knowledge” is disseminated, schools have emerged as the primary channel to instil new national values and patriotism in youth. However, the relationship between education and national identity in Uzbekistan is largely underexplored, and empirical studies are almost non-existent. Notably, Uzbekistani youth perspectives on their national identities and their relationship to the nation remain unknown. To fill this knowledge gap, drawing upon empirical data, including participant observations, photo elicitations, oral history interviews, focus group discussions with university students from various social groups, and textbook analysis, this ethnographically informed study critically examines the role of school education in shaping youth national identities in a complex post-socialist setting. Informed by post-structuralism, which captures identity as non-substantial and shaped through differences with “otherness”, the study explores how school discourses construct national identity through “internal/external others”. It also examines the intersections of national markers such as ethnicity, gender, and religion. By privileging the diverse realities of Uzbekistani youth, the study further analyses how youth learn, perform, negotiate, and resist institutional discourses of national identity construction. The study reveals that school discourses promote positive self-national images of Uzbekistan by extensively drawing boundaries between “us” (Uzbekistan) and “them” (foreign countries and the socialist past). While these discourses do not promote any particular “antagonistic external others”, the “us/them” binary is mostly hierarchical, portraying Uzbekistan as superior. Furthermore, the study indicates the active promotion of ethnicity, gender, and religion as national markers in school discourses. Although some textbook discourses promote inclusivity and equity, these markers primarily centre around dominant social groups such as Uzbeks, men, and Muslims, establishing “internal others” who do not conform. Simultaneously, reflecting the state’s authoritarian secularism, Islam emerged as a complex national marker that youth navigated and negotiated. Despite a singular curriculum, Uzbek-and Russian-medium school practices differed in how they instil national identities, reflecting the role of hidden curriculum in the complex post-Soviet environment. The analysis shows that for many Uzbekistani youth, particularly those from dominant groups, national identity discourses largely overlap with school discourses. However, tensions among youth from different social groups are underscored, especially along ethnic, gender, religious, and linguistic lines. Minority groups expressed frustrations and resistance towards school discourses, revealing discrepancies in their sense of belonging to Uzbekistan. Furthermore, the study shed light on the parallel worlds of students from Uzbek- and Russian-medium schools, who coexist with minimal interaction and distinct national identities. The study highlighted the key role of school education in shaping youth national identities. While acknowledging Uzbekistan’s multi-ethnic and post-socialist context, it emphasises the importance of constructing national identities through less hierarchical “us/them” binaries that reinforce stereotypes of “external others”. Reflecting the population’s heterogeneity, the study calls for more inclusive school discourses, and given the discrepancies in national belonging and tensions among different social groups, less ethnocentric, patriarchal, and authoritarian national markers are crucial for social cohesion.
Keywords: Type of access: Open access; National Identity; Uzbekistan; INTERDISCIPLINARY RESEARCH AREAS::Ethnicity; Gender; Religion; School education